2019
DOI: 10.1111/liv.14251
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 rs738409 is associated with renal glomerular and tubular injury in NAFLD patients with persistently normal ALT levels

Abstract: Background & Aim: Patatin-like phospholipase domain-containing protein 3 (PNPLA3) rs738409 polymorphism is associated with NAFLD severity and the PNPLA3 gene is expressed in the kidneys,but whether PNPLA3 rs738409 polymorphism is also associated with renal tubular injury is uncertain. We assessed the effect of PNPLA3 genotypes on biomarkers of renal tubular injury (RTI) and glomerular function in subjects with NAFLD who had either normal (nALT) or abnormal (abnALT) alanine aminotransaminase levels. Methods: 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
87
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 39 publications
7
87
2
3
Order By: Relevance
“…Increasing evidence now supports the existence of an association between PNPLA3 G/G genotype and decreasing eGFR values or higher prevalence of CKD across different patient population, even after controlling for many CKD risk factors and for the presence of NAFLD [24][25][26][27][28][29][30] (Table 1). For instance, in a cross-sectional study of 740 Japanese individuals (about 16% of whom had NAFLD on ultrasonography), Oniki et al [24], showed that patients with rs738409 G/G genotype had lower eGFR values than those with G/C or C/C genotypes, even after adjustment for multiple cardio-renal and metabolic risk factors.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 99%
See 4 more Smart Citations
“…Increasing evidence now supports the existence of an association between PNPLA3 G/G genotype and decreasing eGFR values or higher prevalence of CKD across different patient population, even after controlling for many CKD risk factors and for the presence of NAFLD [24][25][26][27][28][29][30] (Table 1). For instance, in a cross-sectional study of 740 Japanese individuals (about 16% of whom had NAFLD on ultrasonography), Oniki et al [24], showed that patients with rs738409 G/G genotype had lower eGFR values than those with G/C or C/C genotypes, even after adjustment for multiple cardio-renal and metabolic risk factors.…”
Section: Observational Data Regarding the Role Of Pnpla3 On The Risk mentioning
confidence: 99%
“…Specifically, some variants related to NAFLD risk, including rs738409, show divergent effects between the traditional metabolic alterations and the development of diseases, especially for cardiovascular complications [6,42]. However, at present, accumulating observational data for rs738409 seems to indicate that this single nucleotide polymorphism might be associated to the presence of CKD [24][25][26][27][28][29][30].…”
Section: Pnpla3 In Liver Diseasementioning
confidence: 99%
See 3 more Smart Citations